The Influence of Traditional Navigation Knowledge and the Utilization of Ethnomathematics on the Success of Traditional Fishermen's Operations - Kurniawan, Dwi Agus; Elfaituri, Khaled; Samuel, Ahenkora; Dalhadi, Nehmar J.; Sindu, Sindu (Cahaya Ilmu Cendekia Publisher, 2023)
Purpose of the study: This study aims to analyze the influence of traditional navigation knowledge and the use of ethnomathematics on the success of traditional fishermen's operations in Indonesia. Using a quantitative approach and the Partial Least Squares Structural Equation Modeling (PLS-SEM) method. The survey was conducted on traditional fishermen who have been operating for more than five years, utilizing local navigation knowledge, and applying mathematical principles in going to sea. Methodology: The research instrument was a closed questionnaire with a 5-point Likert scale to measure three main variables: Traditional Navigation Knowledge, Utilization of Ethnomathematics, and Success of Traditional Fishermen's Operations. Data were analyzed through validity, reliability, and structural model tests. Main Findings: results show that traditional navigation knowledge has a significant effect on the success of fishermen's operations with a path coefficient of 0.45 (p = 0.002). The use of ethnomathematics also has a significant effect with a path coefficient of 0.36 (p = 0.005). Overall, the two independent variables explain 60% of the variation in the success of fishermen's operations. This finding emphasizes the importance of integrating local wisdom and scientific approaches to improve the effectiveness and efficiency of traditional fishermen's activities. Novelty/Originality of this study: This research has a novelty by integrating two approaches, namely the influence of traditional navigation knowledge and ethnomathematics, and exploring mathematical concepts in local culture. The results provide an important contribution in developing a model that combines local wisdom and scientific principles to support the sustainability of traditional fishermen's operations in Indonesia.